Effects of stress and burnout on librarians in selected academic libraries in Metro Manila - Caguiat, Cynthia A. (2001)
The study focused on the effects of stress and burnout on librarians in selected academic libraries in Metro Manila. It was conducted to: (1) determine the level of burnout; (2) identify the sources of job-related stress; (3) determine manifestations fo stress; (4) describe the level of burnout which affect job performance in relation to the following personal and professional characteristics, such as, civil status, age, educational attainment, position/designation in the library, and length of employment in the library; and (5) identify the individual coping mechanisms and stress reduction techniques provided by their organizations.